Phosphodiesterase 5 Inhibitor for Pediatric Pulmonary Arterial Hypertension: A Cost-Utility Analysis (2023)
Objectives: Despite the growing evidence of efficacy, scarce information exists regarding the cost of tadalafil to improve the functional classes of pediatric patients with pulmonary arterial hypertension. This study aims to determine the cost-utility of tadalafil compared sildenafil to treat pediatric patients with pulmonary arterial hypertension in Colombia. Methods: A Markov model was developed to compare expected costs, outcomes, and quality-adjusted life-years of sildenafil and tadalafil in pediatric patients with pulmonary arterial hypertension. The model was analyzed probabilistically, and a value of information analysis was conducted to inform the value of conducting further research to reduce current uncertainties in the evidence base. Cost-effectiveness was evaluated at a willingness-to-pay value of US $5180. Results: The mean incremental cost of tadalafil versus sildenafil is US $15 270. The 95% credible interval for the incremental cost ranges from US $28 033.65 to US $5940.86. The mean incremental benefit of tadalafil versus sildenafil is 1.00 quality adjusted life-years (QALY). The 95% credible interval for the incremental benefit ranges from 1.88 to 0.31 QALY. The expected incremental cost per QALY is estimated at US $15 286. There is a probability less than 1% that tadalafil is more cost-effective than sildenafil at a threshold of US $5180 per QALY. Form the value of information analysis, the theoretical upper bound on the value of further research was US $9.298 for Colombia. Conclusion: Our economic evaluation shows that tadalafil is not cost-effective regarding sildenafil to treat pediatric patients with pulmonary arterial hypertension in Colombia. Our study provides evidence that should be used by decision-makers to improve clinical practice guidelines.